Preliminary bioactivity study of comfrey and azalea solutions on red spinach germination - Susanti, Dian; Rahmawati Wijaya, Nur; Samsu Adi, M. Bakti; Widodo, Harto (Agriculture and Natural Resources, 2025)
Importance of the work: Allelopathy allows certain plants to influence the growth of neighboring species through chemical release. While azale (Rhododendron simsii) and comfrey (Symphytum officinale) are known for their allelopathic effects, their impact on vegetable crops like red spinach remains unclear. This warrants further investigation into their potential use in sustainable cultivation systems. Objectives: To determine the bioactivity of comfrey and azalea on the growth of red spinach seeds. Materials and Methods: A completely randomized design was used with two treatment factors: allelopathic plant type (comfrey and azalea) and solution concentration (25%, 50% and 100%). The control was distilled water. Results: Comfrey and azalea had lethal concentration 50% values greater than 100%. Comfrey and azalea concentrations of 25−100% affected almost all measured germination growth parameters. Comfrey and azalea at 25-50% inhibited hypocotyl and cotyledon growth, but at 100% stimulated radicle, cotyledon and biomass growth. Azalea had stronger inhibition activity and weaker stimulatory activity than comfrey. Main finding: Comfrey and azalea at 25−100% concentrations had no phytotoxicity activity. Comfrey and azalea at 25-50% had inhibitory activity, while at 100% they had stimulatory activity. Both test plants had inhibitory and biostimulant activities; this, they have potential for utilization and development as bioherbicides and plant growth regulators. Further research should investigate the inhibitory, stimulatory and allelochemical profiles of comfrey and azalea